1999
DOI: 10.1159/000045427
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Inhibits Transmural Pressure Induced Mesangial Cell Proliferation through Activation of Protein Kinase A

Abstract: Adrenomedullin (AM), a hypotensive peptide isolated from human pheochromocytoma, inhibits the proliferation of mesangial cells (MC) induced by mitogens such as platelet-derived growth factor. Quite recently, we have demonstrated that transmural pressure applied to cultured MC increased DNA synthesis and cell proliferation through protein kinase C and tyrosine kinase pathways. However, the modulatory effect of AM on pressure-induced cell proliferation is as yet unknown. In the present study, we examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…AM was originally identified as a peptide that increases cAMP levels in platelets. 1 Subsequent experiments in mesangial cells yielded results similar to those reported herein 30,31 : AM increased cAMP levels, which led to a PKAdependent decrease in cell proliferation that was associated with decreased ERK activity. It was also shown that delivery of the AM gene attenuates cardiac hypertrophy via production of cAMP 32,33 and that AM cAMP-dependently inhibited DNA synthesis and collagen production in cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
“…AM was originally identified as a peptide that increases cAMP levels in platelets. 1 Subsequent experiments in mesangial cells yielded results similar to those reported herein 30,31 : AM increased cAMP levels, which led to a PKAdependent decrease in cell proliferation that was associated with decreased ERK activity. It was also shown that delivery of the AM gene attenuates cardiac hypertrophy via production of cAMP 32,33 and that AM cAMP-dependently inhibited DNA synthesis and collagen production in cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 72%
“…The intracellular signaling mechanism of AM appears to be cAMP, 29,30 Ca 2ϩ mobilization, 31 inositol-1,4,5-triphosphate, 32 protein kinase A, 33 and mitogen-activated protein kinase pathways. 34 However, there are few reports about the signaling pathways of the suppressive effect of AM on the expression of endothelial adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether AM/AMBP-1 reconstitutes LPS-induced reduction in PPAR-␥ expression, RAW264.7 macrophages were coincubated with AM/AMBP-1 at different concentrations (100 -200 nM AM and 50 -100 nM AMBP-1) based on previous reports (28,29). Four hours of incubation induced a significant increase in PPAR-␥ mRNA expression (Fig.…”
Section: Lps-mediated Inhibition Of Ppar-␥ Expression Is Reconstitutementioning
confidence: 96%